One step ahead: Innovation in core facilities. (14th March 2019) - Lippens, Saskia; D'Enfert, Christophe; Farkas, Lilla; Kehres, Anna; Korn, Bernhard; Morales, Mònica; Pepperkok, Rainer; Premvardhan, Lavanya; Schlapbach, Ralph; Tiran, Andreas; Meder, Doris; Van Minnebruggen, Geert
Abstract : Core facilities—originally founded to give scientists access to a specific technology or service—have expanded to become incubators for new technologies and services. While it has many benefits, it also creates unique problems and challenges.